OPTIMIZATION OF COLD MILLS PRODUCTIVITY - Yavtushenko , Aleksandr; Ptotsenko , Viktor; Saguliakin , Aleksandr (Scientific Journal "Metallurgy", 2020)
The merhod of definition of optimum productivity and technical and economic factors of modern continuous thin-sheet mills cold rolling is resulted and calculations with use of program complex «MathCAD Prime 5» are performed. Influence of main parameters of rolling on a mill productivity is defined. For mills of the basic types boundary rolling rates excess, which performs to decline of mill productivity are determined. Considerable distribution of production and necessity of upgrading of thin-sheet cold-rolled metal require the improvement of existing and creation of new high-performance and economic cold-rolled mills of the cold rolling. The search of optimal parameters of flatting mill is reasonable that he allows to set, on what high speeds of rolling it is expedient to develop new facilities of automation, greasing, cooling systems and to choose the most effective technological parameters of equipment with optimal technical-economy indexes. We will consider dependence of the productivity of flatting mill on speed of rolling on the example of tetracage mill 1700 for rolling of low-carbon steels and motor-car sheet (analogue of mill 1680 of "Zaporozhstal"). At determination of initial parameters and modes of wringing out use these practical the "Mariupol metallurgical combine", where such equipment is set. We build the chart of dependences of change of the average-earned productivity of tetracage mill 1700 from rate of rolling at different mass of rolls by means of function of maximize (Qmidl) "MathCAD Prime 5". Methods over of determination of the optimal productivity and technical-economy indexes of modern continuous stratified mills of the cold rolling are brought. With the use of programmatic complex "MathCAD Prime 5" calculations are executed and influence of basic parameters of rolling (speed of rolling, mass of rolls, rates of acceleration and braking of engines of main occasion, monistic rate of passing of the weld-fabricated guy-sutures, time of auxiliary and fettling operations, mass of hot-rolled rolls before welding, thickness and width stripes which roll) is certain on the productivity of figure. For the mills of basic types maximum rates are certain rolling exceeding of which results in the decline of their productivity